Pengaruh Kepemimpinan Transformasional, Budaya Organisasi dan Work-Life Balance Terhadap Employee Engagement (Studi Kasus Karyawan PT. Bento Group Indonesia Area Malang) - Maulana, Hurin; Pardiman, Pardiman; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine and analyze the influence of Transformational Leadership, Organizational Culture and Work-life Balance on Employee Engagement. This research uses a case employee study of PT. Bento Group Indonesia Malang area uses nonprobability sampling with the technique taken, namely saturated sampling (census). The data analysis methods used in this research are Instrument Test (validity test and reliability test), Normality Test, Classic Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Hypothesis Test (F test and t test), and Test Coefficient of Determination (Adjusted R2). The analysis process uses SPSS. The results of the research state that Leadership, Organizational Culture and Work-Life Balance simultaneously influence Employee Engagement and partially Organizational Culture and Work-Life Balance have a significant influence on Employee Engagement, while Leadership has no influence on Employee Engagement. Keywords: Transformational Leadership, Organizational Culture, Work-life Balance and Employee Engagement.